A Web- and Mobile-Based Intervention for Comorbid, Recurrent Depression in Patients With Chronic Back Pain on Sick Leave (Get.Back): Pilot Randomized Controlled Trial on Feasibility, User Satisfaction, and Effectiveness - Schlicker, Sandra; Baumeister, Harald; Buntrock, Claudia; Sander, Lasse; Paganini, Sarah; Lin, Jiaxi; Berking, Matthias; Lehr, Dirk; Ebert, David (JMIR Mental Health, 2020)
Background: Chronic back pain (CBP) is linked to a higher prevalence and higher occurrence of major depressive disorder (MDD) and can lead to reduced quality of life. Unfortunately, individuals with both CBP and recurrent MDD are underidentified. Utilizing health care insurance data may provide a possibility to better identify this complex population. In addition, internet-and mobile-based interventions might enhance the availability of existing treatments and provide help to those highly burdened individuals.
CRIS-Team WoS Importer:2020-05-12